Aberrant Pregnancy Adaptations in the Peripheral Immune Response in Type 1 Diabetes: A Rat Model. - Bart Groen (Public Library of Science (PLoS), 2013)
Introduction Despite tight glycemic control, pregnancy complication rate in type 1 diabetes patients is higher than in normal pregnancy. Other etiological factors may be responsible for the development of adverse pregnancy outcome. Acceptance of the semi-allogeneic fetus is accompanied by adaptations in the maternal immune-response. Maladaptations of the immune-response has been shown to contribute to pregnancy complications. We hypothesized that type 1 diabetes, as an autoimmune disease, may be associated with maladaptations of the immune-response to pregnancy, possibly resulting in pregnancy complications. Methods We studied pregnancy outcome and pregnancy-induced immunological adaptations in a normoglycemic rat-model of type 1 diabetes, i.e. biobreeding diabetes-prone rats (BBDP; 5 non-pregnant rats, 7 pregnant day 10 rats and 6 pregnant day 18 rats) , versus non-diabetic control rats (i.e. congenic non-diabetic biobreeding diabetes-resistant (BBDR; 6 non-pregnant rats, 6 pregnant day 10 rats and 6 pregnant day 18 rats) and Wistar-rats (6 non-pregnant, 6 pregnant day 10 rats and 5 pregnant day 18 rats)). Results We observed reduced litter size, lower fetal weight of viable fetuses and increased numbers of resorptions versus control rats. These complications are accompanied by various differences in the immune-response between BBDP and control rats in both pregnant and non-pregnant animals. The immune-response in non-pregnant BBDP-rats was characterized by decreased percentages of lymphocytes, increased percentages of effector T-cells, regulatory T-cells and natural killer cells, an increased Th1/Th2-ratio and activated monocytes versus Wistar and BBDR-rats. Furthermore, pregnancy-induced adaptations in BBDP-rats coincided with an increased Th1/Th2-ratio, a decreased mean fluorescence intensity CD161a/NKR-P1b ratio and no further activation of monocytes versus non-diabetic control rats. Conclusion This study suggests that even in the face of strict normoglycemia, pregnancy complications still occur in type 1 diabetic pregnancies. This adverse pregnancy outcome may be related to the aberrant immunological adaptations to pregnancy in diabetic rats.